Hamlet lives in Hollywood : John Barrymore and the acting tradition onscreen - Pomerance, Murray, 1946-; Rybin, Steven, 1979- (Edinburgh : Edinburgh University Press, 2017)
This book, a collection of fifteen original essays on the film performances and stardom of John Barrymore, redresses the lack of scholarship on Barrymore by offering a range of varied perspectives on the actor's work.
8 Prospero Unbound: John Barrymore's Theatrical Transformations of Cinema Reality9 A Star is Dead: Barrymore's Anti-Christian Metaperformance; 10 Handling Time: The Passing of Tradition in A Bill of Divorcement; 11 John Barrymore's Sparkling Topaze; 12 "Planes, Motors, Schedules": Night Flight and the Modernity of John Barrymore; 13 Barrymore and the Scene of Acting: Gesture, Speech, and the Repression of Cinematic Performance; 14 "I Never Thought I Should Sink So Low as to Become an Actor": John Barrymore in Twentieth Century
Vendor-supplied metadata.
Includes bibliographical references and index.
JSTOR
Keywords: Barrymore, John, -- 1882-1942.; Barrymore, John, -- 1882-1942 -- Influence; Barrymore, John, -- 1882-1942; Actors -- United States -- Biography; Acteurs -- États-Unis -- Biographies; PERFORMING ARTS -- Reference; HISTORY -- Middle East -- General; Actors; Influence (Literary, artistic, etc.); United States; Biographies